The contradictions of youth participation for intergenerational justice in urban environmental planning - García-Antúnez, Oriol; Maurer, Megan L.; Gulsrud, Natalie M.; Lundmark, Sofia; Rodela, Romina (Frontiers in Sustainable Cities, 2023)
Intergenerational justice (IGJ) has long been utilized in academic contexts such as philosophy and political theory. However, IGJ has increasingly become politicized. That is, it has been translated into more tangible ideas and discourses for public scrutiny, contestation, and action. This politicization is strongly represented by youth activism, which has utilized the concept to demand urgent political action and to defend the right to be included and represented in decision-making processes, particularly regarding climate change-related issues. The central topic of discussion in this perspective article is the strategic identification of youth inclusion with IGJ, and specifically the risks involved in accepting this identification. In this article we focus on urban environmental planning and argue that it is important to separate the practice of youth inclusion and the concept of IGJ to address these concerns and explore alternative strategies for incorporating IGJ in urban environmental planning. We then proceed to explore potential urban environmental planning approaches that are more intergenerationally just and conclude by critically reflecting on how the current political economy enables or hinders a more intergenerationally just approach to urban environmental planning.